Sternal wound infections after sternotomy: risk factors, prevention and management. (1st June 2022) - Lender, Olga; Göbölös, Laszlo; Bajwa, Gurjyot; Bhatnagar, Gopal
Abstract : A serious complication after cardiac surgery is sternal wound infection. Although incidence rates vary worldwide, this complication raises significant concern in a certain patient demographic. This article uses risk assessment strategies to identify a high-risk patient profile and draws parallels with positive predictors in the preoperative, intraoperative and postoperative setting. It describes the complexity of sternal wound infections and highlights guidelines on detection and treatment. The optimal goal of this article is to help minimise the incidence of sternal wound complications after sternotomy by discussing recommendations for preoperative, intraoperative and postoperative preventive measures.